Effect of Added Tapioca Flour Concentration on the Physicochemical Characteristics of Jeruju Leaf Nori (Achantus ilicifolius) - Septiani, Nur Fitri; Rifki Prayoga Aditia; Devi Faustine Elvina Nuryadin (Jurnal Ilmiah PLATAX, 2026)
Jeruju is one of the mangrove plants that has a fairly high nutritional content and has the potential to be developed as an alternative raw material for making nori. This study aims to determine the effect of the addition of tapioca flour concentration on the physicochemical, organoleptic, and Total Plate Count (TPC) characteristics of orange leaf nori and determine the best treatment. The study used a one-factor Complete Random Design (RAL) with four tapioca flour concentration treatments, namely F0 (0%), F1 (5%), F2 (10%), and F3 (15%) with three replications. The parameters analyzed included moisture content, fat content, ash content, protein content, carbohydrate content, thickness, hedonic test, and Total Plate Count (TPC). The results showed that the addition of tapioca flour had a significant effect (p<0.05) on ash content, protein content, and appearance, but had no significant effect (p>0.05) on moisture content, fat content, carbohydrate content, thickness, aroma, taste, and texture. The moisture content value ranged from 1.33%–2.74%, fat content 18.73%–30.03%, ash content 9.80%–13.68%, protein content 13.16%–15.16%, carbohydrate content 42.18%–52.57%, and thickness 0.16–0.18 mm. The Total Plate Count (TPC) value ranges from 2.09 × 10⁴–9.52 × 10⁴ CFU/g and still meets the SNI 9105:2002 standard. The best treatment was obtained at F2 with the addition of 10% tapioca flour which resulted in the best physicochemical characteristics and preference levels of the panelists. Keywords: jeruju leaves, nori, tapioca flour Abstrak. Jeruju merupakan salah satu tanaman mangrove yang memiliki kandungan nutrisi cukup tinggi dan berpotensi dikembangkan sebagai bahan baku alternatif untuk pembuatan nori. Penelitian ini bertujuan untuk menentukan pengaruh penambahan konsentrasi tepung tapioka terhadap karakteristik fisikokimia, organoleptik, dan Total Plate Count (TPC) nori daun jeruju serta menentukan perlakuan terbaik. Penelitian menggunakan Rancangan Acak Lengkap (RAL) satu faktor dengan empat perlakuan konsentrasi tepung tapioka yaitu F0 (0%), F1 (5%), F2 (10%), dan F3 (15%) dengan tiga kali ulangan. Parameter yang dianalisis meliputi kadar air, kadar lemak, kadar abu, kadar protein, kadar karbohidrat, ketebalan, uji hedonik, dan Total Plate Count (TPC). Hasil penelitian menunjukkan bahwa penambahan tepung tapioka berpengaruh nyata (p<0,05) terhadap kadar abu, kadar protein, dan kenampakan, tetapi tidak berpengaruh nyata (p>0,05) terhadap kadar air, kadar lemak, kadar karbohidrat, ketebalan, aroma, rasa, dan tekstur. Nilai kadar air berkisar antara 1,33%–2,74%, kadar lemak 18,73%–30,03%, kadar abu 9,80%–13,68%, kadar protein 13,16%–15,16%, kadar karbohidrat 42,18%–52,57%, dan ketebalan 0,16–0,18 mm. Nilai Total Plate Count (TPC) berkisar antara 2,09 × 10⁴–9,52 × 10⁴ CFU/g dan masih memenuhi standar SNI 9105:2002. Perlakuan terbaik diperoleh pada F2 dengan penambahan tepung tapioka 10% yang menghasilkan karakteristik fisikokimia dan tingkat kesukaan panelis terbaik. Kata Kunci: daun jeruju, nori, tepung tapioka